2023
DOI: 10.7326/m22-3305
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fluvoxamine With Inhaled Budesonide for Treatment of Early-Onset COVID-19

Abstract: Previous trials have shown the effects of fluvoxamine alone and inhaled budesonide alone for prevention of disease progression among outpatients with COVID-19. This placebo-controlled, randomized trial, conducted at 12 clinical sites in Brazil, sought to determine whether the combined effect of both drugs would increase treatment effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…5 A follow-up TOGETHER trial (n = 1476) testing fluvoxamine 100 mg twice daily with inhaled budesonide in a majority-vaccinated population demonstrated a 50% reduction in the same composite end point. 8 In contrast, the COVID-OUT and ACTIV-6 trials studying fluvoxamine 50 mg twice daily did not identify a benefit for fluvoxamine. 2 Among these studies, ACTIV-6 is the only trial with a primary outcome of patient-reported sustained recovery and, in this trial of fluvoxamine 100 mg twice daily for 13 days, there was no evidence of benefit.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…5 A follow-up TOGETHER trial (n = 1476) testing fluvoxamine 100 mg twice daily with inhaled budesonide in a majority-vaccinated population demonstrated a 50% reduction in the same composite end point. 8 In contrast, the COVID-OUT and ACTIV-6 trials studying fluvoxamine 50 mg twice daily did not identify a benefit for fluvoxamine. 2 Among these studies, ACTIV-6 is the only trial with a primary outcome of patient-reported sustained recovery and, in this trial of fluvoxamine 100 mg twice daily for 13 days, there was no evidence of benefit.…”
Section: Discussionmentioning
confidence: 98%
“…The TOGETHER trial was stopped early for superiority of fluvoxamine 100 mg twice daily, compared with placebo, with a 32% reduction in the primary composite end point of hospitalization or extended care in an emergency setting . A follow-up TOGETHER trial (n = 1476) testing fluvoxamine 100 mg twice daily with inhaled budesonide in a majority-vaccinated population demonstrated a 50% reduction in the same composite end point . In contrast, the COVID-OUT and ACTIV-6 trials studying fluvoxamine 50 mg twice daily did not identify a benefit for fluvoxamine .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations